PREPARATION OF SIMPLE FINANCIAL STATEMENTS FOR MSME ACTORS - Dianty, Astari; Heriyah, N.; Azzahra, Annisa Putri; Pringgakusumah, Alya Putri; Muhlisin, Zihadi Dikri (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
In the world of economics, MSMEs are productive economic businesses owned by individuals or business entities. MSMEs often have difficulty in planning and managing their finances properly. This is usually due to a lack of insight and knowledge about Accounting and the inability of human resources to implement accounting knowledge. Failure to carry out proper recording and use will have an impact on the development of MSMEs because MSMEs will have difficulty in managing managerial activities and showing their business performance so far. Financial Reports function to make economic decisions in determining the investments to be made. Incorrect preparation of Financial Reports will result in incorrect determination of the Cost of Goods Sold. As a result, businesses can experience losses and bankruptcy. Therefore, training is needed to prepare Financial Reports using correct Accounting. As a solution to MSME financial problems, it is necessary to conduct offline sharing sessions with participants, namely MSME business actors in Halal Street Food Malaysia in the form of "Preparation of Simple Financial Reports for MSME actors".